Biofilm growth kinetics and nutrient (N/P) adsorption in an urban lake using reclaimed water: A quantitative baseline for ecological health assessment. (December 2016) - Wang, Tianzhi; Xu, Zhenci; Li, Yunkai; Liang, Mingchao; Wang, Zhenhua; Hynds, Paul
Abstract: Reclaimed wastewater reuse represents an effective method for partial resolution of increasing urban water shortages; however, reclaimed water may be characterized by significant contaminant loading, potentially affecting receiving ecosystem (and potentially human) health. The current study examined biofilm growth and nutrient adsorption in Olympic Lake (Beijing), the largest artificial urban lake in the world supplied exclusively by reclaimed wastewater. Findings indicate that solid particulate, extracellular polymeric substance (EPS) and metal oxide (Al, Fe, Mn) constituent masses adhere to a bacterial growth curve during biofilm formation and growth. Peak values were observed after ≈30 days, arrived at dynamic stability after ≈50 days and were affected by growth matrix surface roughness. These findings may be used to inform biofilm cultivation times for future biomonitoring. Increased growth matrix surface roughness (10.0 μm) was associated with more rapid biofilm growth and therefore an increased sensitivity to ecological variation in reclaimed water. Reclaimed water was found to significantly inhibit biofilm nutrient adsorption when compared with a "natural water" background, with elevated levels of metal oxides (Al, Fe, and Mn) and EPS representing the key substances actively influencing biofilm nutrient adsorption in reclaimed water. Results from the current study may be used to provide a quantitative baseline for future studies seeking to assess ecosystem health via monitoring of biofilms in the presence of reclaimed water through an improved quantitative understanding of biofilm kinetics in these conditions.